Transnational Anti-Communism and the Cold War
XVI, 292 p.
Keywords: How was anti-communism organised in the West? This book covers the agents, aims, and arguments of various transnational anti-communist activists during the Cold War. Existing narratives often place the United States – and especially the CIA – at the centre of anti-communist activity. The book instead opens up new fields of research transnationally.